Self‐Assembly of Mechanoplasmonic Bacterial Cellulose–Metal Nanoparticle Composites. (9th August 2020) - Eskilson, Olof; Lindström, Stefan B.; Sepulveda, Borja; Shahjamali, Mohammad M.; Güell‐Grau, Pau; Sivlér, Petter; Skog, Mårten; Aronsson, Christopher; Björk, Emma M.; Nyberg, Niklas; Khalaf, Hazem; Bengtsson, Torbjörn; et al.
Abstract: Nanocomposites of metal nanoparticles (NPs) and bacterial nanocellulose (BC) enable fabrication of soft and biocompatible materials for optical, catalytic, electronic, and biomedical applications. Current BC–NP nanocomposites are typically prepared by in situ synthesis of the NPs or electrostatic adsorption of surface functionalized NPs, which limits possibilities to control and tune NP size, shape, concentration, and surface chemistry and influences the properties and performance of the materials. Here a self‐assembly strategy is described for fabrication of complex and well‐defined BC–NP composites using colloidal gold and silver NPs of different sizes, shapes, and concentrations. The self‐assembly process results in nanocomposites with distinct biophysical and optical properties. In addition to antibacterial materials and materials with excellent senor performance, materials with unique mechanoplasmonic properties are developed. The homogenous incorporation of plasmonic gold NPs in the BC enables extensive modulation of the optical properties by mechanical stimuli. Compression gives rise to near‐field coupling between adsorbed NPs, resulting in tunable spectral variations and enhanced broadband absorption that amplify both nonlinear optical and thermoplasmonic effects and enables novel biosensing strategies. Abstract : A self‐assembly strategy for fabrication of nanocomposites of bacterial cellulose and metal nanoparticles is described. The nanocomposites display distinct and tunable optical and biophysical properties, including mechanoplasmonic effects. The optical properties can be modulated by mechanical stimuli, which results in large spectral variations and enhanced broadband absorption that amplify both nonlinear optical and thermoplasmonic effects.